Chasing science at sea racing hurricanes, stalking sharks, and living undersea with ocean experts - Prager, Ellen J. (University of Chicago Press, 2008)
To the average office-dweller, marine scientists seem to have the good life: cruising at sea for weeks at a time, swimming in warm coastal waters, living in tropical paradises. But ocean scientists who go to sea will tell you that it is no vacation. Creature comforts are few and the obstacles seemingly insurmountable, yet an abundance of wonder and discovery still awaits those who take to the ocean. Chasing Science at Sea immerses readers in the world of those who regularly go to sea--aquanauts living underwater, marine biologists seeking unseen life in the deep ocean, and the tall-ship captain.